2015
DOI: 10.1007/s10796-015-9583-0
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of ERP assimilation and its impact on ERP value: A TOE-based model and empirical test

Abstract: Drawing on the technology-organizationenvironment (TOE) framework and prior IT assimilation literature, we develop and test an integrated model of ERP assimilation and value in Chinese firms. We also contrast the strength of the antecedents of ERP assimilation and value across different ownership types. Our empirical results using a survey data showed that relative advantage, complexity, compatibility, top management support, organization fit, financial commitment and competitive pressure are significant predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
16

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 67 publications
3
44
0
16
Order By: Relevance
“…For example, Picoto et al studied the influencing factors of retailers' absorption of mobile commerce based on the TOE theory [37]. Xu et al found that the TOE factors have varying effects on absorption of ERP system [38]. Hwang et al applied the TOE theoretical model to study the factors affecting the adoption of the green supply chain in the semiconductor industry [39].…”
Section: B Theoretical Foundationmentioning
confidence: 99%
“…For example, Picoto et al studied the influencing factors of retailers' absorption of mobile commerce based on the TOE theory [37]. Xu et al found that the TOE factors have varying effects on absorption of ERP system [38]. Hwang et al applied the TOE theoretical model to study the factors affecting the adoption of the green supply chain in the semiconductor industry [39].…”
Section: B Theoretical Foundationmentioning
confidence: 99%
“…The TOE model offers a solid theoretical base to gain indepth insight about the adoption of IT innovations and initiatives, and it has been widely used in different IT areas by many scholars to understand the success factors that affect the adoption of new IT initiatives, such as e-commerce [23], cloud computing [24], [25], e-Learning [26], Enterprise Resource Planning (ERP) systems [27], and E-Medical Record (EMR) systems [28]. However, there is lack of studies that employed the TOE to examine the success factors affecting the adoption of green computing in context of universities.…”
Section: Research Modelmentioning
confidence: 99%
“…By the use of ERP, an enterprise can upgrade its core activities to meet the industry standards (Rouhani & Mehri, 2018). ERP implementation benefits can be achieved at numerous levels including management level, operations level, IT hardware level and organizational level (Xu, Ou, & Fan, 2017). ERP is significant software for the progress of a firm (Queiroz, Tallon, Sharma, & Coltman, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers suggested determinants of ERP implementation in multiple industrial sectors and critical factors have been identified in diverse contexts (Ahmed, Shaikh, & Sarim, 2017;Ali, Hussin, Othman, Elzamly, & Doheir, 2018;Baskaran, 2018). Some found the sociological factors and technological aspects (Xu et al, 2017). Few shed light on strategical and procedural facets (Schniederjans & Yadav, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation